An Exploratory Study of How Teacher Type and Experience Relate to Perceptions of Adding More Recess during the School Day. Issue 4 (2nd September 2022) - Erwin, Heather; Thornton, Michelle
Abstract: The primary purpose of this study was to explore elementary faculty perceptions of adding more recess during the school day. Secondarily, authors compared perceptions by teacher type and years of experience. Participants were 25 teachers (representing all grade levels and areas) from one elementary school in the southeastern region of the United States. Participants completed a questionnaire regarding their perceptions toward recess before/after implementing an additional recess period. No significant differences appeared when analyzing data from all participants. However, when examining data by teacher type and experience, a negative statistical significance was found. A school policy of two recess periods per day was perceived less positively by elementary faculty after implementation, and teachers with more experience viewed it more negatively than teachers with less experience. Grade-level teachers were less enthusiastic toward the inclusion of more recess time than administrators, aides, and special area teachers. As school personnel make shifts in school policy related to recess offerings, professional development on the positive outcomes can be geared toward more experienced and grade-level teachers.